Growth charts for Australian children with achondroplasia. Issue 8 (9th June 2017) - Tofts, Louise; Das, Sandeep; Collins, Felicity; Burton, Karen L. O.
Abstract : Achondroplasia is an autosomal dominant disorder, the most common genetic cause of short stature in humans. Reference curves for head circumference, weight, height, and BMI are needed in clinical practice but none exist for the Australian population. This study aimed to produce head circumference, height, weight, and BMI reference percentile curves for Australian children and adolescents with achondroplasia. Measurements of head circumference, height and weight taken at clinical visits were retrospectively extracted from the electronic medical record. Age was corrected for prematurity. Patients were excluded from head circumference analysis if they had significant neurosurgical complications and from the weight and BMI analysis when they had a clinical diagnosis of overweight. Measurements were available on 138 individuals (69 males and 69 females) taken between 1970 and 2015, with over 50% collected since 2005. A total of 3, 352 data points were available. The LMS method was used to produce growth charts with estimated centiles (10, 25, 50, 75, and 90th) separately for males and females. For females birth weight was 3 kg (2.5–3.5 kg), birth length 48 cm (44–50 cm) and head circumference 37.5 cm (36–39 cm), adult height was 125 cm (116–132 cm), weight 42 kg (34–54 kg), and head circumference 58 cm (55.5–60.5 cm) all 50th centile (10–90th). For males birth weight was 3.5 kg (3–4 kg), length 49 cm (46–52 cm) and head circumference 38.5 cm (36–41 cm), adult height was 134 cm (125–141 cm), weight 41 kg (24.5–57 kg) and head circumference 61 cm (58–64 cm). The curves are similar to previously published reference data from the USA and have expected population wide variation from curves from an Argentinian population. Despite limitations of our curves for adolescents (12 years and older) due to data paucity, these Australian growth charts for children and adolescents with achondroplasia will be a useful reference in clinical practice.